2005
DOI: 10.1111/j.1365-2982.2005.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome in developing countries – a disorder of civilization or colonization?

Abstract: While irritable bowel syndrome (IBS) is common in the West, early studies suggest that the prevalence is low in developing countries. However, recent studies point to increasing prevalence in newly developed Asian economies. The presentation appears to differ from the West, with a lack of female predominance, a greater frequency of upper abdominal pain and defecatory symptoms perceived as being less bothersome. This difference, together with the preoccupation with organic disease, could explain why we may be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(157 citation statements)
references
References 63 publications
8
140
1
8
Order By: Relevance
“…27 In contrast to Western patients with IBS who localize pain more frequently to the lower abdomen, Asian patients often appear to localize their pain more frequently to the upper abdomen. 28 In some Asian cultures, food and nutrition have traditionally been viewed as an important aspect of health and of illness. For example, "The Chinese do not draw any distinction between food Hindi HS (n = 10) 10 100% 100% 10 1.000 IBS (n = 10) 10 7 (70%) had FD symptoms also 100% 10 7 (70%) had FD symptoms also 1.000 FC (n = 10) 10 9 (90%) had FD symptoms also 100% 10 9 (90%) had FD symptoms also 1.000 FD (n = 10) 10 6 (60%) had IBS symptoms also 100% 10 4 (40%) had IBS symptoms also 1.000…”
Section: Discussionmentioning
confidence: 99%
“…27 In contrast to Western patients with IBS who localize pain more frequently to the lower abdomen, Asian patients often appear to localize their pain more frequently to the upper abdomen. 28 In some Asian cultures, food and nutrition have traditionally been viewed as an important aspect of health and of illness. For example, "The Chinese do not draw any distinction between food Hindi HS (n = 10) 10 100% 100% 10 1.000 IBS (n = 10) 10 7 (70%) had FD symptoms also 100% 10 7 (70%) had FD symptoms also 1.000 FC (n = 10) 10 9 (90%) had FD symptoms also 100% 10 9 (90%) had FD symptoms also 1.000 FD (n = 10) 10 6 (60%) had IBS symptoms also 100% 10 4 (40%) had IBS symptoms also 1.000…”
Section: Discussionmentioning
confidence: 99%
“…Fatores culturais e decorrentes de hábitos alimentares têm sido isolados com sugestões de agentes etiológicos. 25,26 Hiperalgesia visceral, estresse, abuso físico e sexual têm sido elementos associados como participantes do conjunto de dados clínicos, englobado no universo dessa moléstia [1][2][3][4][5][6][7][8][9] , da mesma forma ocorrendo com as enterites bacterianas e virais, sem que, no entanto, seja possível destacar um elemento marcador. 27,28 São tantas as teorias e complexas as investigações e conclusões que a SCI passa a ser vista sob um conjunto heterogêneo de desordens com sintomas parecidos, mas de diferentes etiologias [29][30][31][32] que retroalimentam mais especulações sobre uma causa básica, o que, sem dúvida alguma, favorece a " medicalização" e a emergência de procedimentos subsidiados pela medicina alternativa 33 .…”
Section: Discussionunclassified
“…32 As upper GI symptoms are common among IBS patients in Asia, patients may be diagnosed as FD and the associated IBS symptoms might be overlooked. 7,33 Two rural and urban population-based studies in Bangladesh using the Rome I and Rome II criteria demonstrated that more than 50% patients with IBS had upper abdominal symptoms. 18,19 Similarly, in a pan-Indian study, 49% of IBS subjects had epigastric pain.…”
Section: Discussionmentioning
confidence: 99%